The influence of the disturbing effect of roadways through faults on the faults' stability and slip characteristics - Shuaifeng Lu; Andrew Chan; Xiaolin Wang; Shanyong Wang; Zhijun Wan; Jingyi Cheng (Deep Underground Science and Engineering)
Abstract In order to mitigate the risk of geological disasters induced by fault activation when roadways intersect reverse faults in coal mining, this paper uses a combination of mechanical models with PFC2D software. A mechanical model is introduced to represent various fault angles, followed by a series of PFC2D loading and unloading tests to validate the model and investigate fault instability and crack propagation under different excavation rates and angles. The results show that (1) the theoretical fault model, impacted by roadway advancing, shows a linear reduction in horizontal stress at a rate of −2.01 MPa/m, while vertical stress increases linearly at 4.02 MPa/m. (2) At field excavation speeds of 2.4, 4.8, 7.2, and 9.6 m/day, the vertical loading rates for the model are 2.23, 4.47, 6.70, and 8.93 Pa/s, respectively. (3) Roadway advancement primarily causes tensile‐compressive failures in front of the roadway, with a decrease in tensile cracks as the stress rate increases. (4) An increase in the fault angle leads to denser cracking on the fault plane, with negligible cracking near the fault itself. The dominant crack orientation is approximately 90°, aligned with the vertical stress.